NEGATIVE POLITENESS STRATEGIES IN ANDREA HIRATA’S NOVEL LASKAR PELANGI - Khair, Muhammad; Manugeren, M.; Purwarno, Purwarno (Universitas Islam Sumatera Utara, 2024)
This research delves into the intricate portrayal of negative politeness strategy in Andrea Hirata's novel Laskar Pelangi. Employing linguistic politeness theory by Brown and Levinson and a structuralism approach, the study aims to elucidate the connection between linguistics and literature within the novel's context. Utilizing a qualitative research methodology, the text is analyzed, focusing on instances of negative politeness strategies employed by characters in various social interactions. Through a descriptive qualitative approach, 53 instances of negative politeness strategies are identified in the novel. The literature review underscores the significance of negative politeness for maintaining rapport and respect in social interactions, particularly in contexts prone to imposition or conflict. Extracted examples from the novel illustrate how characters utilize negative politeness to navigate complex social dynamics and preserve harmonious relationships within their community. The findings reveal cultural nuances embedded in politeness strategies, reflecting Indonesian societal norms and values. Characters in Laskar Pelangi employ indirect speech acts, hedging language, and deferential expressions to mitigate threats to others' autonomy or comfort, contributing to the narrative's tone of warmth and sincerity. Overall, this research highlights the integral role of negative politeness strategies in shaping character interactions and reflecting cultural values in Laskar Pelangi. By employing these strategies, characters negotiate social hierarchies and navigate interpersonal relationships while demonstrating respect and consideration for others.